PERILAKU KEPATUHAN PAJAK: PERSEPSI CALON WAJIB PAJAK POTENSIAL - Feny Destia; Fajar Nurdin (Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to determine potential taxpayers perceptions of tax awareness, tax knowledge, and modernization of the tax administration system on tax compliance behavior. The research method used is the quantitative method. The research was conducted at Faculty of Economic UIN Maulana Malik Ibrahim Malang. Data Source is the primary data with data collection methods, namely the dissemination of questionnaires to respondents and data analysis methods using Partial Least Square (PLS). The population in this study is students of the Faculty of Economics UIN Maulana Malik Ibrahim Malang with sampling techniques using purposive sampling. The results of the study found that based on the perception of potential prospective taxpayers partially or simultaneously tax awareness, tax knowledge, and modernization of the tax administration affect tax compliance behavior. Keywords : Perception, Tax Awareness, Tax Knowledge, Modernization of The Tax Administration, Tax Compliance Behavior